Physical activity levels of children with juvenile idiopathic arthritis. (2nd January 2016) - Condon, Cillin; Morgan, Marie; Ward, Susan; MacDermott, Emma; Killeen, Orla
Abstract: Children with juvenile idiopathic arthritis (JIA) have lower levels of moderate to vigorous physical activity (MVPA) and spend longer in sedentary activities than their peers. A study to assess the physical activity levels at a tertiary Irish centre was undertaken to compare children with JIA in Ireland against the international experience. Children with JIA completed a nine-item validated questionnaire, the Physical Activity Questionnaire for Children (PAQ-C). Pain, medication use and disease subtype were recorded. PAQ-C scores were compared against UK threshold values. Estimated %MVPA and time (min/day) were calculated using a published formula. Fifty-three children with JIA (33 female, 20 male, mean 11.4 years) completed the PAQ-C. Mean PAQ-C level was 2.7 for males and 2.4 for females. One-third of children met the threshold levels for being sufficiently active (normative values 2.9 males, 2.7 females). Using estimated %MVPA, one-third did not achieve 30 min of MVPA. There was no significant difference in PAQ-C levels between children with active disease (active joint count >1, self-reported visual analogue scale pain >1 and elevated erythrocyte sedimentation rate/C-reactive protein) and those without active markers. Using both the PAQ-C and estimated MVPA, only one-third of children with JIA met the recommended 60 min of daily MVPA. This needs to be validated against objective measures, e.g. accelerometers.